Speech at the Multi-Sectoral Conference on Partnerships for Governance and Development - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, noted that we face a worldwide challenge as the population in developing countries grows. What sort of conditions are those people going to live in? Is there going to be equity? Social justice? Peace? The world has changed in the last 50 years, with the private sector and market-oriented economies prevalent, with a more dynamic civil society. In the Philippines, one in three live in poverty. Addressing this must be done in a cooperative way. The Comprehensive Development Framework brings together stakeholders. Social programs will only work if there is an effective structure involving these elements: the first element is strengthening governance; second element is a proper legal and judicial system; third element is the issue of financial supervision and control; fourth element is social system in place; and fifth element is the issue of corruption. The issue of implementation and the issue of transparent review and accountability are tremendously important.